The economic importance and control of termite infestations in relation to plantation forestry and wood preservation in Peninsular Malaysia - an overview - Kirton, Laurence G.; Wong, Andrew H.H (California State University, 2001)
Both the plantation forestry and wood preservation industries in the tropical and sub-tropical belts of the world, exemplified by the humid equatorial Peninsular Malaysia, regard termites as major destructive pests of standing trees, various timber products and building timber structures. This paper is a compilation of information on these economically important pests encountered in both plantation forestry and the wood preservation industry in Malaysia, particularly the peninsula, and describes on-going termite research activities to establish practical control strategies for tree and wood protection.